Fenians, radicals and the Clerkenwell outrage - Irish in Britain History Group, IBHG; Whitehead, Andrew (1984)
Transcript of the talk by Andrew Whitehead, given to the Irish in Britain History Group on 3 May 1984. Includes bibliographical references (p. 19). Photocopied typescript with manuscript amendments.